СТРУКТУРНО-СЕМАНТИЧНІ ОСОБЛИВОСТІ ТА ПЕРЕКЛАД АНГЛІЙСЬКОМОВНИХ ТЕРМІНІВ СФЕРИ АЛЬПІНІЗМУ - Прохоров, Микола Георгійович (Дрогобицький державний педагогічний університет імені Івана Франка, 2024)
The article is devoted to the study of the English-language terminology of the sphere of alpinism. The definition of the notion of terminology of the sphere of alpinism is given in the article, structural and semantic peculiarities, as well as ways of translation of its units are analyzed in it. Attention to transformations used for translation of the analyzed terms by means of the Ukrainian language is also given in the article. The English-language terminology of alpinism is a set of units denoting professional notions of the sphere. Its formation began with the emergence of alpinism as a professional sport sphere. The structure of its terms is heterogeneous. They are represented by words and word combinations. Terms that are words are subdivided into simple root, derivative, complex and abbreviated ones, originating mostly from four-component terminological combinations. Terminological combinations can contain from from two to five components in their structure. The most widespread among them are twoand three-component units formed on the basis of N+N, Adj+N, Part II+N, V + N, N + N + N models. The semantic composition of the English-language terminology of the sphere of alpinism is characterized by the existence of terminologized words of common lexicon, as well as reterminologized words amd metaphoric units, used words and reterminological lexical units, as well as metaphorical terms. Reterminologized terms entered into the Englishlanguage terminology of mountaineering from the spheres of glaciology, physical geography, geology, maritime and fishing, construction and military affairs. Translation of English-language terms of the sphere of alpinism is carried out with the help of terminological equivalents, adaptive transcoding, tracing, as well as descriptively. English-language terminological combinations of the sphere of alpinism are reproduced into the Ukrainian language with the help of simple and complex translating transformations. Simple translating transformations are transposition, omission, adding of words, as well as lexical replacement. Complex transformations contain two or more simple translation transformations. They are widely used in the translation of analyzed terminological units into the Ukrainian language.
Постановка проблеми. Термінологічні дослідження були і залишаються актуальними не тільки через важливість термінів для спілкування фахівців у різних наукових і професійних сферах, але й через проникнення цих одиниць до інших комунікативних сфер, що зумовлює необхідність їх всебічного дослідження задля подальшої систематизації та лексикографічної фіксації.
Keywords: the English language, alpinism, semantics, structural features, ways of translation.